Pengaruh Model SAVI Berbantuan Software Pengendali Client terhadap Tingkat Kedisiplinan dan Hasil Belajar Matematika - Stephanus Lukito Cahyo Purnomo; Dedi Kuswandi; Henry Praherdhiono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
This research aims to determine the effect of SAVI (Somatic, Auditory, Visualization, Intellectually) learning model assisted by client control software on the level of discipline and mathematics learning outcomes in fifth grade. This research design using quasi experimental (quasi experiment) with the form of the nonequivalent control group design. Data collection techniques using observation, interview and test methods. The results showed that the SAVI learning model assisted by client control software had an influence on the level of student discipline in mathematics, but there was no significant difference in student learning outcomes. The conclusion of this study is the SAVI learning model assisted by client controller software has a significant effect on the level of student discipline. The recommendation for further research is that the SAVI learning model can be combined with other media. This research did not take place perfectly due to the Covid-19 pandemic.